Flavivirus Cell Entry and Membrane Fusion - Izabela Rodenhuis-Zybert (Viruses, 2011)
Flaviviruses, such as dengue virus and West Nile virus, are enveloped viruses that infect cells through receptor-mediated endocytosis and fusion from within acidic endosomes. The cell entry process of flaviviruses is mediated by the viral E glycoprotein. This short review will address recent advances in the understanding of flavivirus cell entry with specific emphasis on the recent study of Zaitseva and coworkers, indicating that anionic lipids might play a crucial role in the fusion process of dengue virus [1].